(untitled) (Journal of Applied Business and Economics, 2022)
The application of genetic engineering to food is becoming popular worldwide, especially in UK and USA. However, consumers in Asia remain unsure of the risks and benefits of genetically modified food. To measure the purchase intentions of Taiwanese and Vietnamese consumers using an integrated framework of the attitude model and the behavioral intention model, quantitative research was conducted in which the questionnaires were distributed to respondents living in Taiwan and in Vietnam. The results showed that the dependent variable of consumer attitude was positively impacted by three in-dependent variables including perceived risk to health, perceived benefit to health, and perceived benefit to the environment. The other construct showed no significant effect on consumers’ attitudes in the two countries. The consistency result in both countries between subjective norm and attitude revealed a positive impact on the purchase intention in descending order, while the variable of perceived behavioral control did not contribute to affecting purchase intention significantly. Finally, limitations and suggestions for future studies are also proposed.